Estrategia de publicidad cross-media, en el fortalecimiento historico-cultural de la arquitectura emblemática de Riobamba, mediante la elaboración de pdf´s interactivos - Alexander David, Miranda Guamán (2019)
This research is intended to the promotion and dissemination of the emblematic architectural pieces of Riobamba, which are considered to be of high cultural value, which is why through the development of interactive PDF'S, in conjuntion with the Cross-Media advertising strategy, whose purpose is to promote the historical cultural value. So to determine if citizens know historical places, instruments such as the survey and observation sheets were used. The creative process of the Cross-media advertising strategy is based on the selection of buildings such as; The Cathedral, The Ecuadorian Post Office, The Maldonado High School which are characterized by concentrating unique elements, historical and cultural aspects, as well as structural, be this facade, colors and iconography of them, which will allow us to conduct a study and analysis of each one. According to Bruno Munari and his methodology, the problem was raised, which will help to project the guidelines and elements for the possible solution of the same, through technique or experience, the data collection stage is very important, because it helps to make that the content of the work you do is clearly oriented to the wishes of the target audience. Concluding the Interactive PDF'S, they will be of great help to know to the public about the historical-cultural richness possessed by the architectural pieces of the city of Riobamba, supported by the development with the previous knowledge, obtained throughout the Design career Graphic. Keywords: Cross-Media advertising strategy, Cultural historical strengthening, emblematic architecture, PDF’S, iconography.